Sosialisasi dan Pelatihan MPASI dan Pangan Bergizi Melalui Inovasi Nugget Berbahan Dasar Daun Kelor dan Bayam Merah Bernutrisi (KEMORI) di Desa Sepanjang Jaya Kota Bekasi - Br Karo, Marni; Andi Pranata; Riyen Sari Manullang; Nurhidayah Amir; Dharma Yanti; Uswatun Hasanah; Aliyah Zahra; Nuraini Apriliani; Enjerika Talita Bilqis; Dewi Abela Putri; Choirunnisa Mawardini; Ester Junita Paulina Sitorus; Della Puspita Sari; Syfa Alivia Salmabila; Muhammad Heriandi; Andriyani Putri Kusuma; Cahya Widya Kinanti; Elsa Rosalia Fauziyyah; Raka Rahmatullah; Muhamad Rifki Alfarizi; Husna Mumtaz Maimanah (Universitas Bakti Tunas Husada, 2025)
Nutritional problems in toddlers including stunting, remain a health challenge in the community, particularly due to insufficient intake of nutrients from complementary foods (MPASI). One of the causes is low vegetable consumption among children, even though local vegetables such as moringa leaves and red spinach contain vitamins, minerals, plant-based protein, and antioxidants that are highly beneficial for children's growth and development. This activity aims to educate mothers of infants in Sepanjang Jaya Village, Bekasi City, about the importance of nutritious complementary foods through the KEMORI food innovation (nuggets made from moringa leaves and red spinach). The implementation methods include nutrition education sessions, screening of a video on nugget production, distribution of informational leaflets, and a product tasting session. The results of the activity, attended by 25 participants, showed an increase in knowledge about the nutritional content of local vegetables and the skills to process them into more appealing nuggets for children. In conclusion, the KEMORI innovation can serve as a healthy, practical, and nutritious alternative to complementary foods, while also promoting the use of local food ingredients for stunting prevention and improving the nutritional resilience of infants.